MY SAY: Governance with soul - Abd Razak, Dzulkifli (2009)
Think of Hyderabad and the Charminar — the Four Towers or Mosque of the Four Minarets — comes to mind. It is one of the most important monuments in the city. Collectively with other landmarks, it makes Hyderabad — the capital city of Andhra Pradesh — a very attractive place with its rich history, culture and architecture. It is also a meeting point for North and South India. In recent years, Hyderabad has become an information and technology hub. It has also been abuzz with excitement on news that it is to be home to India's Telugu movie industry — the country's second largest after Bollywood — earning it the nickname Tollywood.